Energy optimization of logistics transport vehicle driven by fuel cell hybrid power system. (1st November 2019) - Lü, Xueqin; Wang, Peisong; Meng, Lingzheng; Chen, Chao
Highlights: A conductivity increment method based on simulated annealing. Li-ion batteries output power dynamic programming. Energy optimization based on equivalent hydrogen consumption. Abstract: To reduce the transportation cost of logistics industry and realize the cleanliness and environmental protection of transportation process, the energy management of logistics transportation vehicles driven by proton exchange membrane fuel cell/Li-ion hybrid power system was studied. Based on the high repeatability of vehicle routing, an energy management strategy is proposed to optimize hydrogen consumption on the premise of ensuring the stability of operation process. To improve the proton exchange membrane fuel cell output characteristics, the maximum power point tracking method based on conductance increment is used, and then the maximum power point, which is seared at the first time, is corrected again by simulated annealing algorithm. The power output control system of Li-ion battery pack based on dynamic programming is also designed. The state variables, control variables, constraint functions, objective functions and cost functions of the drive system are designed according to the related parameters such as vehicle gear change, demand torque and state-of-charge of Li-ion battery pack. The principle of equivalent hydrogen consumption is used to measure the energy output of Li-ion battery, and the fuzzy logic controller is used to simplify the expression of system state and control variables. Finally, the optimal output power sequence of Li-ion battery is calculated. And the experimental results show that after dynamic programming optimization, the driving system can ensure the stable operation of logistics vehicles and greatly reduce the consumption of hydrogen. These results can provide reference for energy management of other types of vehicles driven by proton exchange membrane fuel cell hybrid power system.